THE APPLICATION OF NEW METHODOLOGY IN VOLLEYBALL LABORATORY SELECTION - Dragan Drobnjak; Predrag Nemec (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
In the process of explorative research of transversal character on the model of selected volleyball players numbering 345 players of both sexes from 10 to 19 years of age coming from Montenegrin and Serbian clubs, the validity of selected group of morphological, basic and special motorical indicators used as objective indicators for the level and efficiency of young sportists preparation, has been examined. The examined an throphological space was covered with 51 variables (35 original and 16 derived) that have undergone standard methods of statistical processing (descriptive statistical analysis, inferential and multivariant statistics) resulting in relevant data necessary for conclusions on basic hypothesis of research. The results of research are leading to the following conclusions according to which the morphological - functional space of men and women differs in qualitative manner, can be ascribed to the training factor effect.